2015
DOI: 10.1371/journal.pone.0136629
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons Function as Autocrine and Paracrine Factors to Induce Autotaxin in Response to TLR Activation

Abstract: Lysophosphatidic acid (LPA) is an important phospholipid mediator in inflammation and immunity. However, the mechanism of LPA regulation during inflammatory response is largely unknown. Autotaxin (ATX) is the key enzyme to produce extracellular LPA from lysophosphatidylcholine (LPC). In this study, we found that ATX was induced in monocytic THP-1 cells by TLR4 ligand lipopolysaccharide (LPS), TLR9 ligand CpG oligonucleotide, and TLR3 ligand poly(I:C), respectively. The ATX induction by TLR ligand was abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…LPS-mediated TLR activation of monocytic THP-1 cells was also reported to lead to ATX production [39]. Moreover, it was recently reported that LPA stimulates the expression of F4/80, a well-known macrophage activation marker [4], in bone marrowderived and splenic monocytic (CD11b + ) cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…LPS-mediated TLR activation of monocytic THP-1 cells was also reported to lead to ATX production [39]. Moreover, it was recently reported that LPA stimulates the expression of F4/80, a well-known macrophage activation marker [4], in bone marrowderived and splenic monocytic (CD11b + ) cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is presumed that the finding of elevated C26:0 Lyso-PC in AGS subjects represents a false positive for X-ALD screening. We speculate that elevated C26:0 Lyso-PC, and perhaps elevations in other phosphatidylcholines, may be a marker of an undefined downstream inflammatory pathway in AGS pathophysiology 31; 32 .…”
Section: Discussionmentioning
confidence: 94%
“…26,27 Song et al describe that IFN α/β can act as both autocrine and paracrine signaling molecule, where IFN α and IFN β are producers. 28 Therefore it could be said that inhibition of IFN α/β synthesis may severely affect both autocrine and paracrine activity, which may further lead to impaired immune response (Barth et al 2016). 29 The cellular and molecular changes during and post NiV infection starting right from NiV attachment and invasive pathogenesis leading to multiple organ failure have been explained in the Figures 1, 2, and 3.…”
Section: Cellular and Molecular Changes In Niv Infectionmentioning
confidence: 99%